2242=2(32)g

Rewrite the equation as 2(32)g=2242.

2(32)g=2242

To remove the radical on the left side of the equation, square both sides of the equation.

2(32)g2=(2242)2

Multiply the exponents in ((2(32)g)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(2(32)g)12⋅2=(2242)2

Cancel the common factor of 2.

Cancel the common factor.

(2(32)g)12⋅2=(2242)2

Rewrite the expression.

(2(32)g)1=(2242)2

(2(32)g)1=(2242)2

(2(32)g)1=(2242)2

Multiply 2 by 32.

(64g)1=(2242)2

Simplify.

64g=(2242)2

Multiply the exponents in (2242)2.

Apply the power rule and multiply exponents, (am)n=amn.

64g=2242⋅2

Multiply 2 by 2.

64g=2244

64g=2244

Raise 224 to the power of 4.

64g=2517630976

64g=2517630976

Divide each term in 64g=2517630976 by 64.

64g64=251763097664

Cancel the common factor of 64.

Cancel the common factor.

64g64=251763097664

Divide g by 1.

g=251763097664

g=251763097664

Divide 2517630976 by 64.

g=39337984

g=39337984

Solve using the Square Root Property 224^2 = square root of 2(32)g